Agama Sikh di India: Sejarah Kemunculan, Ajaran dan Aktivitas Sosial-Politik - Muhammad In'am Esha (UIN Maulana Malik Ibrahim Malang, 2006)
The paper examines the Sikhism on its history, doctrines, and political activities. The Sikhism was founded by Guru Nanak whose ideology was initially closed to Islam and further moved to Hindu. However, the political conflict in India between Hindu and Islam is as one strong reason to make eclecticism. Therefore, the doctrines of Sikhism were taken from Islam on one side and Hindu on another side. It results in the Sikhism as a dualistic doctrine in its concept on God, human beings and nature. The Sikhism was involved conflict in India's society when the leader of Sikhism dragged in the political sphere. In the beginning it tried to mediate the conflict between Islam and Hindu. However, it turned to be a trigger into triangle conflict, The Sikh, Islam and Hindu. It becomes obvious that religion is not immune from political conflict, as politics can also become the conflict trigger among religions. Makalah ini mengkaji Sikhisme mengenai sejarah, doktrin, dan aktivitas politiknya. Sikhisme didirikan oleh Guru Nanak yang ideologinya awalnya tertutup bagi Islam dan selanjutnya beralih ke Hindu. Namun, konflik politik di India antara Hindu dan Islam adalah salah satu alasan kuat untuk membuat eklektisisme. Oleh karena itu, doktrin Sikhisme diambil dari Islam di satu sisi dan Hindu di sisi lain. Ini menghasilkan Sikhisme sebagai doktrin dualistik dalam konsepnya tentang Tuhan, manusia dan alam. Sikhisme terlibat konflik di masyarakat India ketika pemimpin Sikhisme menyeret dalam ranah politik. Pada awalnya ia berusaha menengahi konflik antara Islam dan Hindu. Namun, hal itu berubah menjadi pemicu konflik segitiga, Sikh, Islam dan Hindu. Menjadi jelas bahwa agama tidak kebal dari konflik politik, karena politik juga bisa menjadi pemicu konflik antar agama.